Internal Derangement Of Tmj: Conservatıve Approach - Salih Saraçgil; Derviş Yılmaz; Celil Dinçer; Şule Yücetaş (Galenos Yayinevi, 1995)
138 patients with internal derangement of the TMJ were evaluation by the Oral and Maxillofacial Surgery Department of Gazi University Dental Faculty and 94 of these patients were chosen for this study. 43 patients received no therapy whereas 51 had a splint and physical therapy and applied isometric exercises. One year results showed us that 65% of the patients who received therapy had no more complaints and 21% had a great relief 86% clinical success has been achieved. However, in the control group, none of the patients had any improvement.